Nutrition‐sensitive agriculture programme impacts on time use and associations with nutrition outcomes - Mara van denBold; Lilia Bliznashka; Gayathri Ramani; Deanna Olney; Agnes Quisumbing; Abdoulaye Pedehombga; Marcellin Ouedraogo (Wiley, 2021)
Abstract Success of nutrition‐sensitive agriculture programmes targeted to women may be influenced by increased demands on women's and other household members' time and by time‐related trade‐offs to accommodate programme participation. However, evidence of how such programmes impact time use and whether changes in time‐related demands negatively influence maternal or child health and nutrition outcomes is limited. This paper examines the impact of Helen Keller International's Enhanced Homestead Food Production programme in Burkina Faso (2010-2012) on women's and men's time use and associations between changes in women's time use and maternal and child health and nutrition outcomes. We used quantitative data from a cluster‐randomized controlled trial (baseline 2010, endline 2012) and qualitative data from two rounds of process evaluation (2011, 2012). Two‐stage analyses were used to first assess programme impacts on women's and men's time use using difference‐in‐difference impact estimates and second to evaluate whether programme impacts on women's time use were associated with changes in women's and children's health and nutrition outcomes. Programme impacts were considered significant if corrected P < 0.01, and associations were considered significant if p < 0.05 and p < 0.01. Qualitative data were analysed through manual coding and by calculating the means and standard deviations for the time spent by women and men on activities in intervention and control groups. Findings show that the programme significantly increased the amount of time women spent on agriculture in the intervention compared to the control group, but this was not associated with changes in maternal or child health or nutrition outcomes. Process evaluation data supported these findings.